THE LOUISIANA CIVIL CODE. - Saliers, Earl A. (The Accounting Review, 1931)
The article presents information about the Louisiana Civil Code. When compilers of the Louisiana Civil Code of 1825 began their work they found in the French Code the law of ancient Louisiana modernized and readjusted. They used those portions that their experience found applicable to Louisiana, at the same time drawing upon Spanish law in support of principles and practices too well settled to be disturbed. To a large extent, however, they acted independently of both French and Spanish law, so that today there exist, in Louisiana law, many departures from the model after which the fundamental law of the state is patterned. The court reports are replete with cases which illustrate these differences and departures. Thus in Louisiana a last will and testament cannot be annulled for undue influence, because proof is not admitted of the disposition having been made through hatred, anger or suggestion. No attack upon the testamentary capacity of the testator is permitted, except to show that he was mentally incapacitated when he made the will. The presumption of a lucid interval must be overcome, even though the testator has been wholly or partially insane at times before making his will. Death passes decedent's estate to his heirs, hampered only by its administration, if one is desired or necessary or by the limited tenure of an executor in intestate successions.